1997
DOI: 10.1590/s0037-86821997000600004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of IgG and IgM anti-Toxoplasma antibodies in patients with HIV and acquired immunodeficiency syndrome (AIDS)

Abstract: With the emergence of the human immunodeficiency virus (HIV), in patients with acquired immunodeficiency syndrome (AIDS), Toxoplasma gondii has arisen as an important opportunist pathogenic agent, especcially in the central nervous system, being the most common cause of intracerebral lesions. The incidence of Toxoplasma gondii in HIV-infected patients depends principally on the existence of latent Toxoplasma parasitosis in the population affected. Through the enzyme-linked immunosorbent assay (ELISA), IgG and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The high prevalence of latent T. gondii infection in the HIV-infected individuals in our study is consistent with previous reports from Bahir Dar [8] and Addis Ababa [7], in which seroprevalence of 87.4% and 93.3% was documented, respectively. In contrast, relatively low prevalence of T. gondii in HIV-infected individuals was documented elsewhere [24, 25]. …”
Section: Discussionmentioning
confidence: 99%
“…The high prevalence of latent T. gondii infection in the HIV-infected individuals in our study is consistent with previous reports from Bahir Dar [8] and Addis Ababa [7], in which seroprevalence of 87.4% and 93.3% was documented, respectively. In contrast, relatively low prevalence of T. gondii in HIV-infected individuals was documented elsewhere [24, 25]. …”
Section: Discussionmentioning
confidence: 99%
“…Meisheri et al in India reported a prevalence rate of 30.9% and 67.8% in the immunocompetent group and HIV-infected persons respectively 14. Galva Ramirez et al estimated a prevalence rate of 50% in the HIV-infected population in Mexico 15. In Africa, Lindstrom et al evaluated 130 HIV-positive patients in Uganda and estimated a prevalence rate of 54% 16.…”
Section: Discussionmentioning
confidence: 99%
“…It is a public health concern by reason of its neurological manifestations among human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS) patients and the potential association with adverse pregnancy outcomes. [1][2][3][4] The infection is mainly acquired through ingestion of undercooked or raw meat containing viable cysts, ingestion of food and water contaminated with oocysts shed by cats, or congenitally during pregnancy. [5][6][7] The course of the primary infection is often subclinical, with a majority of the infected individuals remaining asymptomatic; few patients may present mild symptoms.…”
Section: Introductionmentioning
confidence: 99%